Water distribution and association in plant vessels and soil pores in a shrub-encroached grassland - Wang, Ruizhe; Zhang, Jialu; Wang, Yuanming; Hu, Xia (Frontiers in Plant Science, 2025)
Woody plant encroachment is a significant ecological challenge for grassland ecosystems worldwide. Soil water is the major limiting factor for plant growth in arid and semiarid grasslands, which are highly vulnerable to woody plant encroachment. Xylem vessels and soil pores are highly associated between aboveground and belowground systems in relation to water utilization of shrubs. Despite their significant role in water processes, how soil pores and vessels are linked associated with water, is unclear. To address this issue, we quantified structures of soil pores and shrub xylem vessels under different shrub encroachment stages and different soil water conditions (low water, moderate water and field capacity conditions) using the X-ray computed tomography. Results showed that proportions of embolized vessel number peaked in the moderate water state of all water conditions (55.71%). Vessels 10–50 μm in size accounted for over 90% of total vessel numbers, and vessels >20 μm had high water conductivity and were vulnerable to water changes. Irregular pores and pores <30 μm retained water, whereas elongated pores and pores >80 μm were conducive to water movement. Soil porosity was positively correlated with vessel diameter, and the correlation was primarily mediated by root development. Positive correlations occurred between water-filled irregular pores and water-filled vessels, especially those <20 μm. Overall, plants primarily took up water stored in irregular soil pores, and this water was held stably within vessels <20 μm. In the context of climate change, the amplified woody plant encroachment might facilitate the development of xylem vessels and soil porosity, which would accelerate the soil drought.